2010
DOI: 10.3390/mca15010079
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Even-Even 114-120Xe Isotopes by the Framework of IBA

Abstract: In this work, the ground state, quasi beta and quasi gamma band energies of 114,116,118,120 Xe isotopes have been investigated by using the both (IBM-1 and IBM-2) versions of interacting boson model (IBM). In calculations, the theoretical energy levels have been obtained by using PHINT and NP-BOS program codes. The presented results are compared with the experimental data in respective tables and figures. At the end, it was seen that the obtained theoretical results are in good agreement with the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…134 Xe The estimated control parameters indicate a spherical to   soft shape transition. The same shape transition is revealed by the evolution of two-neutron separation energies 2n S[29] derived from experimental results[30][31][32][33]. Also, special values are found for the 130 Xe control parameter and 42…”
supporting
confidence: 61%
See 1 more Smart Citation
“…134 Xe The estimated control parameters indicate a spherical to   soft shape transition. The same shape transition is revealed by the evolution of two-neutron separation energies 2n S[29] derived from experimental results[30][31][32][33]. Also, special values are found for the 130 Xe control parameter and 42…”
supporting
confidence: 61%
“…The ground state properties of even-even Xe isotopes have been the subject to theoretical [9][10][11][12][13][14][15][16][17][18] and experimental studies [20] involving in-beam γ -ray spectroscopy. Recently, the nuclear structure of xenon isotopes have been investigated by Turkan in the IBM-1 model [28], while the energy levels, electric quadrupole moments and ( 2) BE values of even-mass nuclei such as Ba , Xe were studied within the framework of the IBM-2 [29][30][31][32][33]. These descriptions suggest these nuclei to 3 be soft with regard to  deformation with a nearly maximum effective trixiality of 30   [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the present study attempts a theoretical investigation of a chain of even-even Xe nuclei within the application of the TPSM approach. In recent times, as well as in the past few decades, various theoretical studies had been used to investigate various nuclear structure properties, such as energy levels, electric quadrupole moments, and B(E2) of the Xe nuclei [14,[17][18][19][20][21]. These studies suggest that these nuclei are soft with regard to the -deformation with a almost maximum effective triaxiality of = [7].…”
Section: A ∼ 130mentioning
confidence: 99%
“…The results were compared with the previous experimental and theoretical data and it has been observed that they are in good agreement. Ismail Maras et al (Maras et al, 2010) studied the ground state, quasi beta and quasi gamma band energies for the 114,116,118,120 Xe isotopes using the interacting boson model (IBM) and calculated the energy levels using PHINT and NPBOS program codes. M. A. Jafarizadeh et al (Jafarizadeh et al, 2013) studied the properties of Xe isotopes in the U(5)↔SO(6) transitional region of IBM and calculated the energy levels and B(E2) transition rates.…”
Section: Introductionmentioning
confidence: 99%